2006
DOI: 10.1093/jjco/hyl121
|View full text |Cite
|
Sign up to set email alerts
|

HSP60 may Predict Good Pathological Response to Neoadjuvant Chemoradiotherapy in Bladder Cancer

Abstract: Positive HSP60 expression prior to CRT may predict good pathological response to low-dose neoadjuvant CRT in invasive or high-risk superficial bladder cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Kamada et al (19) reported that Hsp27 knockdown inhibited tumor growth and enhanced sensitivity to chemotherapy in UMUC-3 human bladder cancer cells. Urushibara et al (20) reported that Hsp60 expression was associated with a good pathological response to neoadjuvant chemoradiotherapy. However, Syrigos et al (21) reported that Hsp70 expression was correlated with tumor grade, stage and overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Kamada et al (19) reported that Hsp27 knockdown inhibited tumor growth and enhanced sensitivity to chemotherapy in UMUC-3 human bladder cancer cells. Urushibara et al (20) reported that Hsp60 expression was associated with a good pathological response to neoadjuvant chemoradiotherapy. However, Syrigos et al (21) reported that Hsp70 expression was correlated with tumor grade, stage and overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Hsp60 is a chaperonin localized to the inner mitochondrial membrane and C. Campanella et al matrix and, less frequently, to extramitochondrial sites (Soltys and Gupta, 1996, 1997Cappello et al, 2008). Hsp60 is constitutively expressed under normal conditions, but its levels can increase (as determined by immunohistochemical methods for example) in pre-neoplastic lesions (Cappello et al, 2002(Cappello et al, , 2003a(Cappello et al, , 2003bFan et al, 2006) and in many advanced cancers (Schneider et al, 1999;Cappello et al, 2005;Urushibara et al, 2007). The main function of the mitochondrial Hsp60 is considered to be assistance in the folding and degradation of mitochondrial proteins (Garrido et al, 2001;Levy-Rimler et al, 2002;Fersht and Daggett, 2002;Parcellier et al, 2003).The involvement of Hsp60 in the process of apoptosis and tumorigenesis is still under debate.…”
Section: Discussionmentioning
confidence: 99%
“…Its overexpression has been reported in exocervix, prostate and colorectal carcinogenesis (44). Hsp60 can be induced by photofrin-mediated photodynamic therapy (PDT) in a PDT-induced resistant colon cancer cell line (45) and is a good prognostic marker to ESCC (44) and neoadjuvant chemoradiation in bladder cancer (46).…”
Section: ------------------------------------------------------------mentioning
confidence: 99%